TRADISI â€œNGEMAI MANDIâ€ ANAK KE SUNGAI SEBAGAI WUJUD CINTA BUDAYA PADA MASYARAKAT DAYAK SEBERUANG DI DESA JAYA MENTARI - Juri, Juri; Yanda, Yuvita (STKIP Persada Khatulistiwa Sintang, 2022)
This research is motivated by the concern of researchers towards the fading of regional culture. Regional culture that used to be so thick in the midst of peopleâ€™s lives as a sign of a fairly harmonius relationship between human beings, human with nature and human with Petara (God). Human at that time believed that if they colud maintain good relations with others, nature and God, the wrath of nature for bad human action could be minimized. This pattern has persisted for centuries. Changing generations, more and more people are inhabiting the earth and the emergence of technology in varoius fields, causes the cultural viscosity that has long been rooted in society, slowly eroding. Before the erosion got worse, we, as a team of researchers who have a strong interest in culture, tried to mix it up return the remains of cultural debris with the hops of generations next you can continue to maintain the culture so that it doestâ€™n just remain a memory. The specific problem in this study includ 1) proses and form of culture playing for the first time bathing in the river, 2) materials of needed to brings children to bathe for the first time in the river, 3) challenges and efforts made by the community in maintaining culture. The results showed: 1) the cultural prosess of bringing a child to take a bath for the first time in the river is still quite thick and is still being preserved, 2) materials needed when taking a child to bathe in the river for the first time include: offerings (pulut rice, white rice, pork, chicken, eth), one white ceramic place, one Gong, one umbrella, one piece of sling cloth, special traditional clothes, for men and woman who charry bathed children, palm wine, and so on, 3) challenges and efforts made, among others: 1) the growing development of humans causes them to be more influenced by foreign culture, the lack of young pople who are interested culture, culture inheritance is more oral, many young pople work in urban areas and others areas, many young people get married, than follow their husbands or wives. The effort made are: involve the younger generation in every traditional activity, make a book about customs, when there are young couples getting married, they are required to marry according to custom and religion. Keywords:Traditions, Bring a children first Time bathing in the River